Evaluation of the Understanding of Home Remedies for Managing Dysmenorrhea Among Adolescent Girls in Selected School of Vaniyamkulam Panchayat - Regina P.F.; Yamunadevi; Danababy; Ardra R.; Arifa. N.A.; Arya Ajayan; Aswani Aji; Aswathy M.V. (International Journal of Women's Health Nursing And Practices, 2024)
Background: India possesses a significant adolescent population critical to its future development. Addressing the health needs of this group is imperative for progress. Dysmenorrhea, characterized by painful menstrual cramps, is prevalent among adolescent girls, and home remedies are commonly used for management. This study aimed to evaluate the knowledge of home remedies for dysmenorrhea among girls at TRK Higher Secondary School in Vaniyamkulam. Objectives: The research had two main objectives: (1) to assess the understanding of home remedies for dysmenorrhea among adolescent girls, and (2) to examine the relationship between their knowledge and specific socio-demographic factors. Methodology: The study included 50 adolescent girls aged 15 to 18 from TRK Higher Secondary School, selected via simple random sampling. Data collection utilized a structured knowledge questionnaire. Statistical analysis comprised frequency analysis and chi-square tests. Results: With a total score of 20, the mean knowledge score was 13.2, representing 66%. Knowledge level distribution indicated 24% of participants had excellent knowledge, 60% had good knowledge, and 16% had average knowledge; none had poor knowledge. The chi-square test yielded a 't' value of 5.99, significant at the 0.05 level, leading to the retention of the null hypothesis, signifying no significant relationship between knowledge of home remedies for dysmenorrhea and the selected socio-demographic variables. Conclusion: The study concluded that while the knowledge level about home remedies for dysmenorrhea is generally good among the adolescent girls studied, this knowledge does not significantly correlate with the demographic variables considered. This suggests that other factors may influence knowledge levels on this topic among adolescents.
Keywords: Adolescent girls; Knowledge; demographic variables; dysmenorrhea; home remedies